(untitled) - Hollerman, Leon (Stanford, California, 1988)
This book focuses on the second phase, particularly on the years from 1980 to 1984, when bureaucratic infighting, interministerial rivalry, and conflict between goverment and business in japan surged into view. Professor Hollerman's lucid explanations of Japanese economic and national strategy make this volume essential reading for anyone interested in Japan's challenge to U.S. bankers, investors, and leaders of transnational corporations
Keywords: Industrial policy,Chính sách công nghiệp; Japan,Nhật Bản